Pengembangan Sistem Pergudangan Sparepart di UPTI. Kayu Pasuruan dengan Menggunakan Metode Research And Development (R&D) - Dzikri, Achmad Maulidan; Asyari, Subchan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research aims to develop a warehousing system that still uses manual methods to record stock of goods, which as a result causes errors in stock calculation, data loss, and difficulty in accurately tracking the movement of goods. In completing this research, research and development (R&D) methods are used to overcome it with stages such as Analysis, Development, and Implementation. Through the development and design of warehousing information systems based on Microsoft Excel and Visual Basic (VBA). The warehouse information system that has been developed provides benefits to UPTI's spare parts warehouse. Pasuruan wood, which is like time efficiency in managing stock of goods, helps in planning the need for spare parts, makes it easier to track goods and reduces the risk of shortages or excess stock.